Re‐expression of Lactotransferrin, a candidate tumor suppressor inactivated by promoter hypermethylation, impairs the malignance of oral squamous cell carcinoma cells. (5th November 2014) - Zhang, Jie; Ling, Tianyou; Wu, Hanjiang; Wang, Kai
<x xml:space="preserve">Abstract</x> Background Lactotransferrin (LTF) has been confirmed to act as a tumor suppressor in multiple cancers; however, its roles in oral squamous cell carcinoma (OSCC), one of malignant head and neck carcinomas, has not been explored. Methods Here, the expression of LTF in OSCC tissues and TCA8113 cells was detected with RT‐PCR, qPCR, and IHC. And the correlation between LTF expression and OSCC metastasis was assessed. MS‐PCR was performed to reveal the methylation status in promoter regions of LTF both in OSCC tissue samples and cells. The influences of 5‐Aza‐Cdc treatment to the methylation status and expression levels of LTF were also analyzed. At last, the functions of LTF in OSCC progression were demonstrated by MTT analysis, clone formation assay, and cell cycle analysis in TCA8113 cells with forced ectopic expression of LTF. Results LTF showed a low or null expression pattern in OSCC tissues and cells, at least partially, due to the hypermethylated status in promoter regions for 5‐Aza‐Cdc, a methyltransferase inhibitor, could restore the expression of LTF in TCA8113 cells. And the expression level of LTF exhibited a negative correlation with OSCC metastasis. Conclusions Re‐expression of LTF inhibited the growth, proliferation, as well as cell cycle progression of TCA8113 cells. In conclusion, hypermethylation contributes much to LTF inactivation in OSCC. And LTF can partially reverse the malignant phenotypes of OSCC cells and may be served as a potential target for diagnosis and therapy of OSCC in future.